DoIt4Me: a tool for automating administrative tasks on Windows NT networks - Augusto, Alessandro; Guimarães, Célio Cardoso; Geus, Paulo Lício de (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2001: Anais do I Workshop em Segurança de Sistemas Computacionais, 2001)
The process to secure a Windows NT computer is simple when the system administrator knows the required configuration settings [13,14]. However, even with this knowledge, to apply the same configuration to hundreds of NT-based computers can be frustrating and laborious. Remote administration of a large Windows NT network is a complex task. The tools provided by standard NT installations are, at best, inadequate. The explosive growth in network sizes over the last years has resulted in large and complex sites but no significant new tools were created. This paper introduces the design and implementation of DoIt4Me, a simple and flexible tool that enables, from a single console, automation of a large number of Windows NT administrative tasks.